Characteristics of users of a tailored, interactive website for parents and its impact on adolescent vaccination attitudes and uptake. (December 2015) - Dempsey, Amanda; Maertens, Julie; Beaty, Brenda; O'Leary, Sean
Abstract Background We examined the characteristics of parents using an iPad-based intervention about vaccines, and its impact on vaccination attitudes and behavior. Methods Interventions were implemented in three primary care clinics from June 2012–September 2013. Baseline and follow up surveys assessed vaccination attitudes and intentions. Medical records were used to examine adolescent vaccine uptake. Results During the study, 42 parents viewed tailored educational content. Users were generally positive about vaccines, though one out of five worried that vaccines caused more harm than good. Among the 16 parents completing the post-intervention survey, there was a slightly higher, non-statistically significant, mean vaccination intention after viewing the website than prior to viewing it for three of the four adolescent vaccines (all except tetanus–diphtheria–acellular pertussis). Using the intervention did not increase the likelihood of adolescent vaccination. Conclusions Providing educational material via iPads in clinic waiting rooms does not appear to be an effective strategy for engaging parents about vaccines. Overall, parents' interaction with TeenVaxScene was low, and had little impact on their vaccination attitudes and beliefs. However, use of TeenVaxScene did not appear toworsen parents' attitudes about vaccines. New and creative ideas for engaging parents to use such educational materials are needed.